Evaluasi Program One Muhammadiyah One Response (OMOR) Dalam Penanggulangan Bencana Alam: Sebuah Studi Observasi di Kabupaten Magelang Indonesia - Margono, ABS; Amin, Muhammad Khoirul; Handayani, Estrin (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Indonesia is a region where natural disasters, such as earthquakes, tsunamis, volcanic eruptions, floods,landslides, and others have potentially happened. Natural disasters that occur in Indonesia generally havecaused facilities, material losses, and psychological impacts. Muhammadiyah Central Management DisasterManagement Agency has an English term